2019
DOI: 10.3390/en12224315
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mixed-Flow Fans with a Newly Shaped Diffuser on Heat Stress of Dairy Cows Based on CFD

Abstract: Mixed-flow fans (MFF) are widely used to reduce the heat stress in dairy cows in summer. Our research team developed MFFs with a newly shaped diffuser with the length of 250 mm and the circumferential angle of 150°, which have better performance in terms of maximum flow flux and energy efficiency. However, how the elevation angle of the diffuser influences the performance of MFFs and how the optimal fan perform in the field experiment has not been studied yet. In this paper, the diffuser was optimized by CFD (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…The CFD model of the cooling pad proposed, presented good agreement with the experimental as was established for the RMSE values computed. High relative differences in the dry-bulb temperature and relative humidity predictions were obtained in the validation process of the CFD model of the barn, which similar ones were reported by Yao et al [ 42 ]. These differences could be attributed to several factors.…”
Section: Discussionsupporting
confidence: 85%
“…The CFD model of the cooling pad proposed, presented good agreement with the experimental as was established for the RMSE values computed. High relative differences in the dry-bulb temperature and relative humidity predictions were obtained in the validation process of the CFD model of the barn, which similar ones were reported by Yao et al [ 42 ]. These differences could be attributed to several factors.…”
Section: Discussionsupporting
confidence: 85%
“…Economic calculations show that the introduction of such a system will reduce ventilation costs by up to 5%. Research results (Yao et al, 2019) showed that a diffuser with an inclination angle of 10° works better than with an elevation angle of 0°, achieving an increase in jet stream length of 0.5 m and an increase in energy efficiency of 1.39%. This was achieved due to the greater axial wind speed and better coefficients of uneven flow distribution at the level of dairy cattle.…”
Section: Solutions and Challengesmentioning
confidence: 99%
“…Sometimes, when calculating such indices (e.g., the equivalent temperature index ETIC, etc. ), additional variables are taken into account that can increase or decrease the heat load, such as solar radiation or air velocity (Maderet al, 2006;Wang et al, 2018b;Yao et al, 2019).…”
Section: Problematic Issuesmentioning
confidence: 99%
“…In tropical countries like India, the extreme weather conditions such as summer with high temperature result in decreased performance by farm animals. Positive results are seen with physical modification of the environment such as shading and fans, when applied for lactating buffaloes (Ahmad et al, 2019) and in dairy cows using mixed-flow fans (Yao et al, 2019). However, direct water spraying over animals using sprinkler systems is the one of the most effective way to combat heat stress (Tresoldi et al, 2019).…”
Section: Artificial Intelligence To Manage Heat Stress and Milk Produ...mentioning
confidence: 99%